2015
DOI: 10.1016/j.molp.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Major Latex Protein 28 Functions as a Positive Regulator of the Ethylene Responsive Factor 6 in Defense against Verticillium dahliae

Abstract: In this study, we identified a defense-related major latex protein (MLP) from upland cotton (designated GhMLP28) and investigated its functional mechanism. GhMLP28 transcripts were ubiquitously present in cotton plants, with higher accumulation in the root. Expression of the GhMLP28 gene was induced by Verticillium dahliae inoculation and was responsive to defense signaling molecules, including ethylene, jasmonic acid, and salicylic acid. Knockdown of GhMLP28 expression by virus-induced gene silencing resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 57 publications
8
106
1
Order By: Relevance
“…Verticillium wilt is a type of vascular disease caused by the soil-borne fungus Verticillium dahliae, and it is the most destructive disease of cotton (Gossypium hirsutum) production (Gao et al, 2013a;Yang et al, 2015). Unfortunately, there is no Verticillium wilt immune germplasm in the widely planted upland cotton .…”
Section: Ghcpk33 Negatively Regulates Defense Against Verticillium Damentioning
confidence: 99%
“…Verticillium wilt is a type of vascular disease caused by the soil-borne fungus Verticillium dahliae, and it is the most destructive disease of cotton (Gossypium hirsutum) production (Gao et al, 2013a;Yang et al, 2015). Unfortunately, there is no Verticillium wilt immune germplasm in the widely planted upland cotton .…”
Section: Ghcpk33 Negatively Regulates Defense Against Verticillium Damentioning
confidence: 99%
“…From 14 transcripts matching MLPs, 11 were consistently repressed (Supplementary Figure S5V). Although the function of these proteins has not been completely elucidated, there is evidence of their regulation through hormone signaling (Ruperti et al, 2002; Yang et al, 2015; Wang et al, 2016), and activation in response to pathogens (Schenk et al, 2000; Kiirika et al, 2014; Yang et al, 2015). However, our results were opposite to these studies and we found only one study were 16 major latex proteins were repressed in response to oxidative stress in Arabidopsis (Stanley Kim et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Transient expression assays were performed as described by Yang et al (2014). Approximately 1.7 kb upstream of StICS1 was amplified from genomic DNA by PCR and cloned into pGWB435 (Invitrogen) to generate the StICS1 Pro :Luc reporter construct.…”
Section: Transient Expression Assaymentioning
confidence: 99%